In the Position of "Persons unsuitable for reproduction" / Documents Attesting to the Sterilization of Roma from the Protectorate during World War II - Viková, Lada (Romano džaniben, 2019)
This material study reflecting and analysing testimonies that include forced sterilization written by Romani women imprisoned during WWII in concentration camps is both a probe into the content of their requests for compensation for forced medical surgeries, and also an effort to contextualize their compensation applications. Examined applications for the compensation of Nazi medical experiments contain archival records from 1964--1973. The study provides concrete testimonies by Romani women who have been involuntarily and forcibly sterilized, records of medical examiners and testimonies of doctors who tried to support the applicants and their compensation claims. Emphasis is put on ethical aspects regarding the use of the documents presented here for research.
Keywords: Romani women; forced sterilisation; Nazi medical experiments; post-war testimonies; Clauberg´s experiments